Why Do Some People Still Fail to Utilize Affordable Non-Communicable Diseases (NCDs) Screening Services?: a Qualitative Study Among White Collar Workers in Depok, West Java, Indonesia - Rachman, Andre; Hadi, Ella Nurlaella; Setio, Kartika Anggun Dimar (Indian Journal of Community Health, 2018)
Background: Indonesia Basic Health Research (IBHR) 2013 results show that Depok citizens were at risk of non-communicable diseases (NCDs). However, participation on NCDs screening test among white collar workers was still 46.4%. Aim & Objective: The aim of this study is to explore barriers and challenges in accessing and implementing NCDs screening service at City Hall Depok. Methods and Material: This research used qualitative method. The data were collected through focus group discussion, in-depth interview, and document review. Results: The knowledge of informants about NCDs and NCDs screening needs improvement. The barriers for participating in NCDs screening were: tight work schedule, lack of information about NCDs screening programs, long queue, fear of an existing disease, and attention to the privacy of participants. Conclusions: Policy support and cooperation both across programs and sectors will be needed for future improvement. Education concerning NCDs and NCDs screening must be improved to engage utilization.